2010
DOI: 10.1177/1074840709358405
|View full text |Cite
|
Sign up to set email alerts
|

Research on Caregiving in Chinese Families Living With Mental Illness: A Critical Review

Abstract: Much of the existing research on caregiving in families of individuals with mental illness has been conducted in Western societies. Therefore, the purpose of this review was to critically examine research on caregiving in families of individuals with mental illness living in Taiwan, Hong Kong, and Mainland China. A search using computerized databases, public search engines, and references from retrieved articles revealed 37 studies published from 1990 to 2009. Four studies were theory driven at an individual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 64 publications
(170 reference statements)
4
30
0
1
Order By: Relevance
“…In the present study, findings suggest that female family caregivers are more likely than their male counterparts to experience the costs of caregiving without adequate resources. Much of Taiwanese caregiving literature to date had showed that positive effects of social support on adaptation of family caregivers; however, caregivers and families have continued to struggle with the limited provision of support because of lack of identification of special needs of family caregivers (Hsiao & Van Riper 2010), such as gender‐specific support. Further, caregiving literature seldom recognises the importance of gender‐related caregiving circumstances, which may contribute to changes in social support (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, findings suggest that female family caregivers are more likely than their male counterparts to experience the costs of caregiving without adequate resources. Much of Taiwanese caregiving literature to date had showed that positive effects of social support on adaptation of family caregivers; however, caregivers and families have continued to struggle with the limited provision of support because of lack of identification of special needs of family caregivers (Hsiao & Van Riper 2010), such as gender‐specific support. Further, caregiving literature seldom recognises the importance of gender‐related caregiving circumstances, which may contribute to changes in social support (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The caregivers not only provide the basic care such as long-term assistance of housing and financial aid, but also have to monitor the patient’s mental state, supervise the patient to take medicine on time, identify the early signs of illness, provide emotional support, and help patient access services [20]. The caregivers are expected to assume a variety of roles, so it is understandable that their levels of MHL will affect the patient’s mental status and rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Confucian beliefs about fate and the forces of heaven may provide a source of emotional support for caregivers to adapt to adversity when they face challenges related to the child's disability (Huang et al, 1998). Chinese family caregivers with Confucian beliefs may be better able to endure hardship and overcome challenges related to caring for a child with a disability (Hsiao & Van Riper, 2010;Lin, 2014).…”
mentioning
confidence: 96%